Dampak Perceraian Orang Tua Terhadap Psikis dan Aktivitas Belajar Anak - Nurya Putri Wulandayu; Hanifa Sahaja Putri; Nur Hanyk Martina; Wahyu Feby Yulianingsih (Jurnal Pendidikan Tuntas, 2023)
The background of this research is to analyze the impact of parental divorce on children. Divorce itself is defined as the end of the relationship between husband and wife which is carried out in several stages based on law and religion. Changes in attitude, emotional stability, and responsibility are the psychological impacts of divorce as well. Changes in children's attitudes, namely feeling inferior, children becoming shy, difficult to socialize with, and like to be alone. This kind of attitude shows that the child's psychology is disturbed due to depression because his parents are divorced. Apart from changes in attitudes, children's responsibilities also change, where a child should have responsibility for education, like to lighten or help parents, after divorce children become more like playing and lose responsibility. On the emotional side, kuja children are disturbed, their minds are depressed and suffering, they feel guilty, they feel embarrassed about their environment, all of which gives rise to inner conflict. Keywords: impact of divorce, children, parents